DIGITAL TECHNOLOGIES FOR IMPROVING THE RELIABILITY OF POWER SUPPLY FACILITIES (Web of Technology: Multidimensional Research Journal, 2026)
This article explores the role of digital technologies as a means of improving the reliability of railway traction power supply. The importance of digitalization in implementing the Central Asian Republic Development Strategy is emphasized. Current challenges and their solutions are identified. The organizational and practical aspects of digital technologies are considered. A classification system for devices, objects, failure modes, wear, and misalignment of measuring systems, devices, and automation, as well as contamination and aging, is proposed.